Gestión contable de los pasivos de la empresa In Planet S.A 2019 – 2020 - Torres Bravo, Day Stephany (2021)
This case study is based on the company In Planet S.A, which offers its clients internet bandwidth and fiber optics.This study is focused on carrying out a study of the accounting management of the liabilities of the company that is located in the city of Babahoyo The case study is focused on carrying out the accounting management of the liabilities of the company in planet sa, which allows knowing the accounting results of the company through the financial statements that it presents, which will allow, the losses arising during the last years 2019 -2020 To collect the information, an interview was applied to the company's employees in order to know its financial status, the main purpose of this investigation is to show the owner how the company is financially currently. For this study, the bibliography of pages, web, books, magazines of works from previous and current years was used.